ANALISIS PENGGUNAAN EFFECTIVE ENGLISH COMMUNICATION DALAM MENDESKRIPSIKAN TEMPAT WISATA SERTA KONSERVASI BUDAYA DAN ALAM DI BALI - Ni Made Milati; Kadek Yuniari Suryatini (Program Studi Pendidikan Biologi Universitas PGRI Mahadewa Indonesia, 2024)
This study was conducted with two objectives: 1) How is the use of English used by students? 2) To find out effective methods of communication for students so that later this study requires a comprehensive and systematic study. The benefits developed are that they can provide a positive impact for BEC Academy students in improving their English communication skills. The theoretical benefits of the results of this study are expected to enrich the knowledge of students' effective English communication skills in explaining a tourist spot in good and correct English. In addition, the results of this study can be useful for the development of English speaking skills and can be a reference for further scientific research. This type of research uses a descriptive analytical research method. This method is used to analyse students' abilities in effective English communication.